2023
DOI: 10.1186/s12937-023-00840-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E intake on glycemic control and insulin resistance in diabetic patients: an updated systematic review and meta-analysis of randomized controlled trials

Abstract: Since a 2014 meta-analysis, several randomized controlled trials (RCTs) evaluating the effect of vitamin E intake on glycemic indices and insulin resistance in adults with diabetes have reached inconsistent conclusions. Therefore, we updated the previous meta-analysis to summarize the current evidence in this regard. Online databases including PubMed, Scopus, ISI Web of Science, and Google Scholar were searched to identify relevant studies published up to September 30, 2021, using relevant keywords. Random-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…Moreover, our study revealed no clear associations of both vitamins A and E with T2D incidence. These findings are consistent with other studies, which showed no significantly different correlations between the vitamin A and E status and the risk of T2D [16,38,39]. Another explanation might be because of an adequate intake of both vitamins, which was found in our study groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, our study revealed no clear associations of both vitamins A and E with T2D incidence. These findings are consistent with other studies, which showed no significantly different correlations between the vitamin A and E status and the risk of T2D [16,38,39]. Another explanation might be because of an adequate intake of both vitamins, which was found in our study groups.…”
Section: Discussionsupporting
confidence: 93%
“…Vitamin E (α-tocopherol) is an important natural lipophilic antioxidant. It helps ameliorate high blood glucose concentrations [16]. Vitamin E levels are also reportedly lower in patients with T2D than in those without T2D; supplementation of this vitamin could delay diabetic complications because it aids in reducing ROS formation [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…A countless number of studies unveiling the antidiabetic properties, including early preventive, disease course modifying, and complication limiting effects, of individual nutrients and phytochemicals that are ubiquitously present in BP from different botanical and geographical origins have been published so far. This includes, for example, nutrients including vitamins such as groups B [ 241 , 242 , 243 ], C [ 244 , 245 , 246 ], D [ 247 , 248 , 249 ], and E [ 128 , 250 , 251 ], oligo-elements and other minerals [ 252 , 253 , 254 ], and lipids such as unsaturated fatty acids [ 255 , 256 , 257 ] and phytosterols [ 63 , 258 , 259 ], as well as other phytochemicals including polyphenols such as phenolic acids, flavonoids, and stilbenes (very recent and comprehensive reviews of preclinical and clinical evidence can be found in [ 260 , 261 , 262 , 263 , 264 , 265 , 266 ]). Despite the substantial amount of experimental and clinical evidence of all these BP compounds in the complex pathophysiology of diabetes and in its interaction with other comorbidities, the possible synergistic potential and real clinical outcome of these compounds, which are always combined in BP, have generally been omitted in research and must be further studied by in vivo experiments, and subsequently verified and objectively assessed by clinical studies.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate management procedure for malnutrition in diabetes mellitus patients has not still been established. Zn [130,131], vitamin E [132], folate [133], and L-arginine [134,135] supplementation and fiber-rich diets [136] have been suggested to potentially improve blood glucose control and insulin resistance. The reason why L-arginine improved glycemic control and insulin resistance is not clear in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc (Zn) [130,131], vitamin E [132], folate [133], and L-arginine [134,135] supplementation and fiber-rich diets [136] may improve glycemic control and insulin resistance (IR) in type 2 diabetes mellitus patients. The Mediterranean diet may improve glycemic control [137] and reduce cardiovascular diseases risk [137,138].…”
Section: Diabetes and Nutritionmentioning
confidence: 99%